Boric acid-based ternary deep eutectic solvent for extraction and oxidative desulfurization of diesel fuel. Issue 11 (17th May 2019) - Jiang, Wei; Jia, Hao; Li, Hongping; Zhu, Linhua; Tao, Runming; Zhu, Wenshuai; Li, Huaming; Dai, Sheng
Abstract : Ternary deep eutectic solvents were used for ODS of fuels (DESs) for the first time although most research continues to be focused on binary DESs. Abstract : Deep eutectic solvents (DESs) have been intensively investigated as promising "green" solvents for a range of industrial processes, although most research continues to be focused on binary DESs. This paper reports on a class of ternary DESs formed by choline chloride (ChCl), polyethylene glycol (PEG), and boric acid (BA) that may be viewed as a new system for extraction and oxidative desulfurization (ODS) of diesel fuel. Compared with organic acid-based DESs, ternary DESs offer advantages including low volatility, low toxicity, and high activity. After tuning the molar ratio of the three compositions, sulfur removal reached 99.2% in 2 h at 60 °C when the molar ratio of H2 O2 to dibenzothiophene was 6. The binary DESs, ChCl/PEG and ChCl/BA, showed unsatisfactory extraction and oxidation efficiency. The reaction mechanism identified through experimental and theoretical methods showed that superoxide radical may be the main active oxygen species, and BA-based peroxides may also play an important role. The results of this study may expand the use of BA and supply a new class of DESs for ODS and other possible applications.